Economics for business - Sloman, John, 1947-; Sutcliffe, Mark, M.Sc. (London ; New York : Pearson Education, 2004)
It is a direct and readable textbook with a firm focus on applying economic principles to the real world of business.
Includes index.
uaj 18/09/2014
Loans
Keywords: Economics; Business; Commerce; Great Britain -- Economic policy -- 1945-; Great Britain -- Commercial policy